SIDS-Focused Green Economy: An Analysis of Challenges and Opportunities - United Nations Environment Programme (United Nations, 2016)
In this Synthesis Report, five development sectors for Small Island Developing States (SIDS) - small-scale fisheries and aquaculture, water, tourism, energy and solid waste - are analysed in an attempt to show how a transition to a green economy can assist in addressing some of the most critical challenges SIDS face while stimulating economic development, maintaining economic stability, facilitating job creation while conserving resources. These sectors are not only inter-related, but also reflect the SIDS’ challenges as they relate to land and water scarcity, dependence on imported energy, high costs associated with waste management and the vulnerability and fragility of the tourism sector. This Synthesis Report will seek to show how a transition to a green economy can contribute to advancing sustainable development in SIDS.